#TITLE_ALTERNATIVE# - HERLAMBANG (NIM 20806002), ARIF
Outstanding claims liability is the insurance companies corporate responsibility towards future debt. There are a number of existing models used to estimate the outstanding claims liability for long tail business. However, some of the assumptions imposed on these models are not met by the claims data under consideration. Furthermore, trends in the development year and payment year periods are not taken into account by these models. The Probabilistic Trend Family (PTF) model is developed to overcome these problems. In this thesis, PTF model is described; and the process of estimating the outstanding claims liability, starting from the preliminary analysis of the claims data to the estimation of the outstanding claims liability is explained. Furthermore, the sensitivity of the obtained estimate of the outstanding claims liability is analyzed using a tool called leverage. Leverage can be used to evaluate the robustness of the model used to estimate the outstanding claims liability.